Patient perception of Breezhaler® and Ellipta® device feedback mechanisms in COPD: The ADVANTAGE Study. (1st February 2019) - Altman, Pablo; Bergna, Miguel A.; Garcia, Gabriel R.; Guerin, Tadhg; Pino, Andrea V.; Whiteford, John L.
Abstract: Objectives: The primary objective of the ADVANTAGE study was to compare device-naïve chronic obstructive pulmonary disease (COPD) patients' perception of the Breezhaler ® and Ellipta ® devices' feedback mechanisms of dose delivery confirmation. The secondary objective was to assess comfort with the inhalers' mouthpiece in terms of ease to form a tight seal around the mouthpiece. These objectives were achieved by using a novel, patient perception of inhaler questionnaire developed and tested during cognitive interviews of patients by Evidera, London, United Kingdom. Methods: Ten COPD patients were interviewed to collect feedback on the interpretation, relevance and language of the questionnaire. This questionnaire was then used in ADVANTAGE to compare patients' perception ( n = 100) of both devices. Patients completed the questionnaire after a single inhalation of placebo through each inhaler. Results: Using the final questionnaire, patients reported being more confident of the feedback mechanism of Breezhaler than that of the Ellipta device (mean score 4.3 versus 3.6 respectively, estimated difference [95% CI]: 0.75 [0.51, 0.99], p < .0001). Patients also reported better comfort (ease to form a tight seal with the lips) with the Breezhaler mouthpiece than the Ellipta mouthpiece (mean score 4.3 versus 3.9 respectively, estimated difference [95% CI]: 0.41 [0.21, 0.61], p < .0001). There were no safety concerns associated with either device. Conclusion: COPD patients showed greater preference for the Breezhaler over the Ellipta inhaler for confidence of dose delivery and comfort of the mouthpiece. Trial registration: ClinicalTrials.gov identifier: NCT02551224.